PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DI KELAS VIII SMP NEGERI 1 PALUPUH - Mutia Sarah (Departemen Matematika, 2022)
The goal of learning mathematics is to grow problem-solving skills, but in reality, participants' ability to solve mathematical problems remains low. One of the efforts that can be made to overcome the problem is the use of a problem-based learning model. The research method used is quasi experimental research with a Nonequivalent Control Group Design research design. Based on the results of the final test data analysis, it was concluded that the application of the problem-based learning model has an effect on the ability of mathematical students to solve problems, such that the mathematical problem-solving skills of students who learn with the problem-based learning model are superior to those of students who learn with the direct learning model.. Keywords– Problem Based Learning Model, Mathematics Learning, Mathematical Problem SolvingSkills